Somos un arco iris - Tabor, Nancy (New York : Scholastic, 1995)
Simple text and illustrations explore some of the similarities and differences that a child recognizes after moving to the United States from a Spanish-speaking country.
Spanish and English.
Keywords: Ethnology -- Juvenile literature; Individual differences -- Juvenile literature; Ethnicity; Individuality; Diferencias individuales